IDENTIFIKASI SITUASI BERBAHAYA ANAK 5-6 TAHUN MELALUI VIDEO YOUTUBE DANGEROUS THING - Subhan Subhan (Jurnal Panrita, 2023)
The aim of this research is to increase children's understanding in identifying dangerous situations both for themselves and others. Selected as research subjects were children from group B of the Kampung Baru Islamic Kindergarten who were still experiencing obstacles in this aspect of their development. The subject's problem was resolved through two cycles of classroom action research (PTK), namely cycle I and cycle II. Data collection techniques use observation techniques and instruments, namely observation guidelines to see the achievement of research targets related to current problems. The results of data analysis show that increasing children's understanding in identifying dangerous situations can be improved through the application of random YouTube video learning media with the theme of dangerous things in group B of the Kampung Baru Islamic Kindergarten. The entire series of actions have gone according to plan and as expected. Children's ability to recognize dangerous situations can be improved starting from pre-cycle data from the results of the researcher's initial observations up to cycle I and cycle II. The achievement of the KKM is sufficient evidence that the actions in this research are significant in improving aspects of child development in this research.